Late Pleistocene - Holocene vegetation and climate from the palaeolake sediments, Rukti valley, Kinnaur, Himachal Himalaya. (20th June 2018) - Ranhotra, Parminder S.; Sharma, Jyoti; Bhattacharyya, Amalava; Basavaiah, N.; Dutta, Koushik
Abstract: Vegetation and climate during later part of Pleistocene to major part of Holocene (∼16.6–3.5 ka) has been reconstructed based on the palynological and magnetic susceptibility proxies from an exposed section of lacustrine deposit at Rukti, Sangla valley, Kinnaur, western Himalaya. Study shows that along with the general tree line succession to higher altitudes since early Holocene, the area has also captured the major climatic events of late Pleistocene to early-mid Holocene time. The area exhibits a continuation of mixed conifer - broadleaved forest at least since ∼16.6 ka with intermittent phases of expansions of broadleaved tree taxa especially Oaks ( Quercus ) or invasion of conifers especially Pine ( Pinus ) with an increase (moist) or decrease (dry) of Indian Summer Monsoon (ISM) respectively. This is also supported by the variations in the magnetic susceptibility values. The climate was warm and moist during ∼16.6 ka and changed to cool ∼13.3 ka, followed by increasing ISM since ∼11.5 ka. Distinct spike in the magnetic susceptibility values between ∼8.7 and ∼7.8 ka could correspond to global 8.2 ka cool event thus indicating strengthening of westerly influence and low evaporation. Subsequent warm conditions could be generalized by the advancement of Birch ( Betula ) line to higher altitude following the resultant retreat of the glacial body. Study has put forth the potential of such Himalayan sites to uncover the major climatic events of global correlation captured by various proxies within a region.